Evaluasi Titer Antibodi Pasca Vaksinasi Septicaemia epizootica Pada Sapi Bali Di Kota Kupang - Cantona, Mario Herryaldo; Sanam, Maxs U.E; Utami, Tri; Tophianong, Tarsisius C; Widi, Antin Y.N (Jurnal Veteriner Nusantara, 2024)
Controlling Septicemia epizooticae (SE) through vaccination program has been undertaken in Kupang City. However, numbers of fatal cases are still being reported. The purpose of this study is to measure the antibody titer of Bali cattle after SE vaccination, and to determine the effect of age and sex on antibody titers. The 50 serum samples of SE vaccinated Bali cattle were taken from Alak Sub-district (26 samples) and Maulafa Sub-district (24 samples). The selection of sub-districts in Kupang City was taken in a simple random manner. Those serum samples were examined using the indirect enzyme-linked immunosorbent assay (ELISA) method. Antibody titers against SE is declared to be protective when the antibody titer is above 88 ELISA Unit (EU). Results indicated that average value of cattle antibody titer after the SE vaccination was able to trigger a protective antibody response (> 70 EU), meanwhile ONE WAY ANOVA analysis results showed that there is no significant effect (P> 0.05) of cattle age towards antibody titers. In the same way, the paired t test results did not indicate a difference in the value of antibody titers against the sex of the Bali cattle.